Core@shell, Au@TiOx nanoparticles by gas phase synthesis. Issue 19 (3rd May 2017) - Martínez, L.; Mayoral, A.; Espiñeira, M.; Roman, E.; Palomares, F. J.; Huttel, Y.
Abstract : Gas phase synthesis and characterization of core@shell, Au@TiOx nanoparticles is reported. Abstract : Herein, gas phase synthesis and characterization of multifunctional core@shell, Au@TiO x nanoparticles have been reported. The nanoparticles were produced via a one-step process using a multiple-ion cluster source under a controlled environment that guaranteed the purity of the nanoparticles. The growth of the Au cores (6 nm diameter) is stopped when they pass through the Ti plasma where they are covered by an ultra-thin (1 nm thick) and homogeneous titanium shell that is oxidized in-flight before the soft-landing of the nanoparticles. The Au cores were found to be highly crystalline with icosahedral (44%) and decahedral (66%) structures, whereas the shell, mainly composed of TiO2 (79%), was not ordered. The highly electrical insulating behaviour of the titanium oxide shell was confirmed by the charging effect produced during X-ray photoemission spectroscopy.